The Phenomenon of Social Interaction in Arabic Language Content on TikTok: A Netnography Study - Mustofa, Syaiful; Faisol, Faisol; Asrofik, Asrofik; Nida Husnia Ramadhani; Rinda Eka Mulyani (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
Language is reflection of culture. With advancement of technology, interactions not limited to face-to-face communication but also occur online, creating a digital environment. This study aims to explore how netizen interactions (man-to-man) on TikTok shape public perceptions of Arabic language through cultural dimensions, as well as how social media algorithms contribute to the formation of these perceptions (man-to-machine). Using a qualitative critical analysis approach with netnography method, the study examines interactions among netizens in comment sections, revealing two main cultural perspectives: Arabic as a religious language and as a poetic language. NLP-based sentiment analysis shows that Arabic is valued not only for its religious function but also for its beauty. Moreover, human machine interactions via algorithms influence content exposure and shape public perceptions. The findings highlight that public opinion about language is constructed through both social interactions and algorithmic mechanisms, expanding understanding of relationship between language, culture, and media.